Securing the Connected World: A Review Paper of IoT Security Architecture, Challenges, and Emerging Solutions - Mohammed Hassn, Baraa (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2025)
This survey provides a systematic review of IoT security by conducting a strict examination of over 200 research papers published during 2014-2023 and ultimately shortlisting the most significant contributions based on citation importance and relevance. The major findings show that conventional security solutions are increasingly inadequate to address the specific challenges of IoT environments predicted to connect 84 billion devices by 2025. Our research identifies critical security vulnerabilities at the perception, network, and application layers, while examining the prospects of new solutions including blockchain, artificial intelligence, and edge computing solutions. The integration of these technologies shows promising results in strengthening IoT security, even though deployment challenges remain in resource-constrained environments. Domain-specific findings depict the need for tailored security frameworks for industrial, healthcare, and home automation systems. This survey concludes that future IoT security requires scalable, autonomous, and adaptive defense mechanisms that can overcome exponentially increasing threats while providing interoperability on heterogeneous platforms.